CHRONICLE OF SPANISH HEALTH LEGISLATION 2017-2018 - RIVERO, Antonio PIGA; BARREDA, ñigo; LAREDO, Asunción FERNÁNDEZ; ALFONSO-GALÁN, María Teresa (MEDECINE LEGALE DROIT MEDICAL, 2025)
This chronicle of Spanish health legislation, which covers the two years 2017 and 2018, makes it possible to note the impact of changes in national policy in the field of health. Indeed, in June 2018, the People’s Party (PP) government, chaired by Mariano Rajoy (2011-2018), lost the confidence of the Parliament, and Pedro Sán-chez, leader of the Socialist Party, was invested as the new President of the Spanish Government. In turn, Mr. Sánchez, who governs without a majority, has had to face the crucial questions of the management of the National Health Service without implementing the necessary reforms.